2020
DOI: 10.1088/1755-1315/564/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

The effect of several types of mangrove exctracs on tiger shrimp Penaeus monodon survival rate challenged with White Spot Syndrome Virus (WSSV)

Abstract: This experiment was aimed to determine the survival rate of tiger shrimp on the use of several types of mangrove extracts challenged with the White Spot Syndrome Virus (WSSV). The experiment was conducted in November 2015 at the Research Institute for brackish water Aquaculture and Fisheries Extension (RIBAFE), Maros. The plastic container of 40 L volume was filled with 30 L of seawater at a salinity of 28 ppt which had been disinfected with chlorine powder of 150 ppm and neutralized with Sodium Thiosufateof 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Indonesia has abundant natural resources, including mangrove forests, so its utilization can be studied as an alternative treatment for shrimp ponds, including treating WSSV diseases. Previous research showed that several mangrove species growing in pond areas in South Sulawesi could be used to produce antibiotics, anti-vibriosis, and anti-WSSV [18][19].…”
Section: ____________________________mentioning
confidence: 99%
“…Indonesia has abundant natural resources, including mangrove forests, so its utilization can be studied as an alternative treatment for shrimp ponds, including treating WSSV diseases. Previous research showed that several mangrove species growing in pond areas in South Sulawesi could be used to produce antibiotics, anti-vibriosis, and anti-WSSV [18][19].…”
Section: ____________________________mentioning
confidence: 99%
“…The death rate of tiger shrimp is greatly decreased by this concentration [4]. The treatment with the highest mean survival rate for tiger shrimp was the one that used S. alba diethyl ether extract [5]. Compared to other therapies, the administration of 250 ppm of Avicennia alba leaf extract is more successful in treating vannamei shrimp infected with V. harveyi [6].…”
Section: Introductionmentioning
confidence: 99%